2013
DOI: 10.20460/jgsm.2013715668
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effects of Individual Competencies on Performance: A Field Study in Services Industries in Turkey

Abstract: This study aims to analyze the effects of individual competencies on performance in the services industries in Turkey. A survey research was conducted in this study. The survey was addressed to the companies in service sector in Turkey, and the questionnaires have been distributed to 3000 employees in 30 companies and 2679 completed questionnaires were returned, representing a response rate of 89 percent. An exploratory factor analysis (EFA) was used to assess the influence of individual competencies on perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 27 publications
9
49
0
12
Order By: Relevance
“…The results of this study were in line with the previous research conducted by [11]- [13] who explained that competence affects the performance of employees. Performance and effectiveness of employees in performing the task is determined by the competencies required by the field of work.…”
Section: Advances In Social Science Education and Humanities Researcsupporting
confidence: 92%
“…The results of this study were in line with the previous research conducted by [11]- [13] who explained that competence affects the performance of employees. Performance and effectiveness of employees in performing the task is determined by the competencies required by the field of work.…”
Section: Advances In Social Science Education and Humanities Researcsupporting
confidence: 92%
“…Abbaszadeh et al (2012) in his research results concluded that the increased of managers competence can improve the employee performance or productivity. And the results of Yunus research (2009) which states that the higher level of employee competence, then the performance of employees will increase.Then with the increasing of employees competence, it will have an impact on organizational performance (Zaim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The competences, as a measurement tool, identify behavioral factors relevant to performance in the job and viewed as how the job is carried out. Hence, many organizations use the competency models as a part of their employee development program to appraise behavioral performance indicators together with objectives (Özçelik and Ferman, in Zaim et al, 2013 ).…”
Section: Competence Employeementioning
confidence: 99%